Usefulness of pelvic ultrasonography for the diagnosis of central precocious puberty in girls - Jung Yu; Ha Young Shin; Sun Hee Lee; You Sung Kim; Jae Hyun Kim (Korean Pediatric Society, 2015)
PurposeIt is difficult to differentiate between central precocious puberty (CPP) and premature thelarche (PT) in girls. The aim of this study was to investigate the diagnostic usefulness of pelvic ultrasonography to distinguish between CPP and PT in girls with early breast development.MethodsThis study included girls with early breast development who visited the clinic between January 2012 and December 2013. Clinical, laboratory, and pelvic ultrasonographic data were evaluated. CPP and PT were confirmed using the gonadotropin-releasing hormone stimulation test.ResultsA total of 248 girls aged 7-8 years were included, among whom 186 (75.0%) had CPP and 62 (25.0%) had PT. The uterine length, transverse diameter, fundus, volume, and cross-sectional area were significantly larger in the CPP group (uterine length, 2.45±0.50 cm vs. 2.63±0.49 cm, P=0.015; uterine volume, 0.95±0.62 cm3 vs. 1.35±0.76 cm3, P<0.001). However, there were no differences in the fundus/cervix ratio and ovarian measurements. In receiver operating characteristic analysis, a uterine volume of at least 1.07 cm3 was the most predictive parameter for CPP with an area under the curve of 0.670 (95% confidence interval, 0.593-0.747).ConclusionUterine measurements by pelvic ultrasonography in girls with early pubertal development were significantly larger in the CPP group. However, the diagnostic value of ultrasonographic parameters was not high because of a considerable overlap of values between the two groups. Therefore, pelvic ultrasonography in combination with clinical and laboratory tests may be useful to distinguish between CPP and PT in girls.